Answer:
3t^2s
Step-by-step explanation:
15/3=5
t^5s/t^2s = t^3
t^2s^3/t^2s = s^2
Answer:
see the explanation
Step-by-step explanation:
we know that
g(x)=2f(x)
so
Find the value of g(x) for the corresponding value of f(x)
1) For x=-6, f(x)=2
Substitute
g(x)=2f(x)
g(x)=2(2)=4
2) For x=-2, f(x)=2
Substitute
g(x)=2f(x)
g(x)=2(2)=4
3) For x=0, f(x)=6
Substitute
g(x)=2f(x)
g(x)=2(6)=12
4) For x=1, f(x)=3
Substitute
g(x)=2f(x)
g(x)=2(3)=6
4) For x=6, f(x)=-1
Substitute
g(x)=2f(x)
g(x)=2(-1)=-2
I think the answer is the one in the bottom right.
Answer:
10 is your answer
Step-by-step explanation:
Note that the side given to us has a measurement of 5 for one of the legs of the isosceles.
This means that the <em>1</em> side on the 30-60-90 triangle has a measurement of 5.
Now, note the measurements of the triangle sides for a 30-60-90 triangle. They measure at: 1 , √3 , 2.
the side 1 is given to us, at 5. You are solving for the hypothenuse (2). Multiply 2 to the side 1
5 * 2 = 10
10 is your answer
~